Socio-Territorial Movements and the Combat Hunger During the New Coronavirus Pandemic in Brazil - Albuquerque Jorge, Aline [UNESP]; Dos Santos Machado, Angela [UNESP] (Universidad Nacional de Colombia, 2023)
In Brazil, the working class has been losing rights and suffering with the discontinuation of public policies. The current government’s actions have been reflected in the increase of extreme poverty and, consequently, in the country’s return to the hunger map. The new coronavirus pandemic has aggravated this circumstance. It is in this context that the food donations made by the Movimento dos Trabalhadores Rurais Sem Terra (mst) [Landless Rural Workers Movement] and other socio-spatial and socio-territorial movements constitute important solidarity actions aimed at combating hunger. This work seeks to critically analyze and dimension the mst’s food donations. To do so, we executed bibliographic research and semi-structured interviews. It also sought and systematized news articles published by the mst, referring to donations made from March 2020 to March 2021. The survey indicates that food donations are a form of resistance and denouncement of the public power’s absence and expressing solidarity. These actions reaffirm the need for a land reform.
Movimientos socioterritoriales y lucha contra el hambre durante la pandemia por el nuevo coronavirus en Brasil
Os movimentos socioterritoriais e a luta contra a fome durante a pandemia do novo coronavírus no Brasil
Keywords: Brazil; coronavirus; food donation; Landless Rural Workers Movement; socio-spatial movements; socio-territorial movements; space; territory